Modeling and Evaluation of Erosion Wear Suspension System - Upadhayay, Lalit (Thapar University, 2010)
A proper understanding of the phenomenon of wear in slurry pipelines is essential for any designer of a slurry transportation system. In view of this, many investigators have developed erosion wear test rigs, among which the slurry pot tester is common. Suspension system of a slurry pot tester plays a vital role in accurate evaluation of wear rate. Therefore, the need for the study and optimization of solid-liquid suspension, specifically in the pot tester has arisen. The primary objectives of solid-liquid mixing are to avoid solid accumulation in the agitated vessel, to maximize the contacting area between the solids and liquid, and to ensure the system is homogeneous or solids particles are uniformly distributed throughout the vessel. A lot of work has been reported in the literature regarding solid-liquid suspension in large stir tanks and reactors used in chemical mixing and dispersion. In the present investigation, solid concentrations at various cylinderical heights are determined experimentally and then compared with simulation results obtained by using Eulerian-granular model. Four different types of PBT propellers are used in the experiments. Experimental results are taken at 3 different impeller speeds and solid concentrations and compared with the corresponding simulation results. Effect of the provision of baffle clearance on solid-liquid suspension in the slurry pot tester has also been studied in the present investigation. Commercial CFD code FLUENT has been used to generate the simulation results. A multiple reference frame approach was adopted to simulate the impeller rotation in the baffled cylinderical tank of the pot tester. Solid-liquid suspension in the pot tester has been examined quantitatively by calculating relative standard deviations of both the experimental and simulation results.
M.E. Production and Industrial Engineering
Keywords: Sluury Suspension; Erosion wear; Pot tester